2019
DOI: 10.1136/bmj.l5337
|View full text |Cite
|
Sign up to set email alerts
|

Penicillin V four times daily for five days versus three times daily for 10 days in patients with pharyngotonsillitis caused by group A streptococci: randomised controlled, open label, non-inferiority study

Abstract: Objective To determine whether total exposure to penicillin V can be reduced while maintaining adequate clinical efficacy when treating pharyngotonsillitis caused by group A streptococci. Design Open label, randomised controlled non-inferiority study. Setting 17 primary healthcare centres in Sweden between September 2015 and February 2018. Participants Patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 29 publications
0
38
0
1
Order By: Relevance
“…A recent study reported that carriage cleared in 156 of 194 children and adults aged 6 years or older randomized to penicillin 800 mg qid for 5 days (80%) versus in 165 of 182 randomized to 1000 mg tid for 10 days (91%; difference −10.2%, 95% CI −17.8 to −2.7%). 74 Symptoms resolved earlier with the higher daily dose but rates of clinical cure at 5–7 days, relapse and complications were equivalent with the two regimens. To sum up, the optimal duration of treatment with oral penicillin to prevent RF is not known but 10 days is slightly more likely than 5 days to clear carriage.…”
Section: Treatment Of Pharyngitismentioning
confidence: 90%
“…A recent study reported that carriage cleared in 156 of 194 children and adults aged 6 years or older randomized to penicillin 800 mg qid for 5 days (80%) versus in 165 of 182 randomized to 1000 mg tid for 10 days (91%; difference −10.2%, 95% CI −17.8 to −2.7%). 74 Symptoms resolved earlier with the higher daily dose but rates of clinical cure at 5–7 days, relapse and complications were equivalent with the two regimens. To sum up, the optimal duration of treatment with oral penicillin to prevent RF is not known but 10 days is slightly more likely than 5 days to clear carriage.…”
Section: Treatment Of Pharyngitismentioning
confidence: 90%
“…GAS pharyngitis is a treatable condition. The antibiotic of choice is mainly penicillin, and in patients with penicillin allergy, cephalosporin or macrolides can be used [10][11][12]. The treatment of GAS is paramount to avoid complications.…”
Section: Discussionmentioning
confidence: 99%
“…(30) Another study also showed equivalent clinical cure but slightly less (80% vs 90%) bacterial eradication in the 5 day group compared to 10 days of penicillin. (31) Guidelines from the United Kingdom recommend a 5-10-day course of penicillin (10 days if recurrent infection) whereas the Canadian Pediatric Society recommends 10 days of oral penicillin or amoxicillin. (Top, Sauve et al, In Press) (32)…”
Section: Streptococcal Pharyngitismentioning
confidence: 99%